Ketidakadilan Gender dalam Novel Bidadari Berbisik Karya Asma Nadia - Chairany Yandi Fitri; Yenni Hayati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
The main objective of this research is to describe gender inequality in the novel Whispering Angel by Asma Nadia. This form of gender inequality includes five forms, namely marginalization, subordination, stereotypes, violence and excessive workload. The causes of gender inequality consist of four factors, namely, caste factors, attitude factors, economic factors and social factors. From the act of gender injustice there is an impact of the action, which is divided into three impacts namely, psychological impact, moral impact and the impact of the destruction of idealism. Gender injustice is not only felt by women, but sometimes men are also in that position. Nowadays, the perpetrators of gender injustice are not only perpetrated by men against women but also by women against women as told in the novel Whispering Angel by Asma Nadia. This type of research is literary research using descriptive methods. The research data are in the form of words, phrases, clauses, sentences, narration from the narrator, the speeches of the characters, and the actions of the characters related to gender inequality. The data collection method uses the listening method with advanced techniques in the form of note taking techniques. Data analysis techniques with content analysis, consisting of data reduction, data presentation, and data verification. The data validation technique uses the triangulation technique. The novel Whispering Angel by Asma Nadia focuses on social problems that often occur in society, namely gender issues. This is of course related to the sociological theory of literary works, reflecting what it is because the author connects directly with cases of gender inequality that occur in Indonesia. Thus, the author's way of expressing his concern about the case, the author makes victims of acts of violence as one of the story characters whose function is to convey the author's message to his readers. So that readers can care more and empathize with the problems that occur in social life.